Detectors for selective registration of charged particles and gamma-quanta - Ryzhikov, V.; Starzhinskiy, N.; Katrunov, K.; Gal’chinetskiy, L.; Chernikov, V.; Zelenskaya, O.; Krivonosov, E.; Litvinov, L.; Galkin, S.; Loseva, E. (Вопросы атомной науки и техники, 2002)
A new design is proposed and described of a combined detector (CD) for simultaneous detection of charged particles and gamma-quanta. The CD comprises a single crystalline plate of ZnSe(Te) placed onto the output window of a scintillating transparent light transducer made of CsI(Tl) and Al₂O₃(Ti) in the shape of truncated pyramid. The CsI(Tl) light transducer is used to create an additional channel for detection of gamma-radiation, as well as for protecting the photodiode from the penetrating radiation. It is shown that introduction of such light transducer does not worsen the energy characteristics of ZnSe(Te). Separate detection of alpha- and gamma-radiation has been achieved under simultaneous excitation by ²³⁹Pu (ZnSe(Te), Ra = 6 %) and ²⁴¹Am (CsI(Tl), Rγ = 20 %). The use of selective optical filters allows separation of the peaks of total absorption (p.t.a.) in the case of their superposition.